Human guanylate binding proteins: nanomachines orchestrating host defense. (12th January 2021) - Kutsch, Miriam; Coers, Jörn
Abstract : Disease‐causing microorganisms not only breach anatomical barriers and invade tissues but also frequently enter host cells, nutrient‐enriched environments amenable to support parasitic microbial growth. Protection from many infectious diseases is therefore reliant on the ability of individual host cells to combat intracellular infections through the execution of cell‐autonomous defense programs. Central players in human cell‐autonomous immunity are members of the family of dynamin‐related guanylate binding proteins (GBPs). The importance of these interferon‐inducible GTPases in host defense to viral, bacterial, and protozoan pathogens has been established for some time; only recently, cell biological and biochemical studies that largely focused on the prenylated paralogs GBP1, GBP2, and GBP5 have provided us with robust molecular frameworks for GBP‐mediated immunity. Specifically, the recent characterization of GBP1 as a bona fide pattern recognition receptor for bacterial lipopolysaccharide (LPS) disrupting the integrity of bacterial outer membranes through LPS aggregation, the discovery of a link between hydrolysis‐induced GMP production by GBP1 and inflammasome activation, and the classification of GBP2 and GBP5 as inhibitors of viral envelope glycoprotein processing via suppression of the host endoprotease furin have paved the way for a vastly improved conceptual understanding of the molecular mechanisms by which GBP nanomachines execute cell‐autonomous immunity. The herein discussed models incorporate our current knowledge of the antimicrobial, proinflammatory, and biochemical properties of human GBPs and thereby provide testable hypotheses that will guide future studies into the intricacies of GBP‐controlled host defense and their role in human disease. Abstract : The ability of any single cell of our body to defend itself against intracellular pathogens is a critical aspect of the human immune system. Many of our cells' intrinsic defenses are orchestrated by a set of guanylate binding proteins (GBPs). Here, we synthesize recent studies to generate a comprehensive model for the biochemical and cell biological mechanisms by which GBPs defend against protozoan, bacterial, and viral pathogens.